2017
DOI: 10.1155/2017/8707289
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Oxidation of Carbon Monoxide over Mesoporous Au-Fe2O3Catalysts

Abstract: Low temperature active and stable mesoporous Au (0.1, 0.2, 0.5, and 1.0 wt.%) supported -Fe 2 O 3 catalysts were prepared via deposition-precipitation method. The H 2 -pretreated catalyst with 0.5 wt.% Au loading offered CO conversion of 100% at 323 K and showed continual activity for at least 120 h. X-ray diffraction and transmission electron microscopy analysis indicate that Au species were highly dispersed as nanoparticles (20-40 nm) on the surface of -Fe 2 O 3 support even after thermal treatment at 773 K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 67 publications
2
10
0
Order By: Relevance
“…The chemical shift of L3 lines likely results from oxygen vacancies, which partially decrease the oxidation states of Fe cations from Fe 3+ to Fe 2+ . 44,45 By comparing the degree of chemical shift of L3 lines, it can be concluded that Fe2O3-S has the maximum amount of oxygen vacancies, followed by Fe2O3-C and Fe2O3-R, in accordance with the result of oxygen K-edge energy loss ( Figure 6A). 3.3.…”
Section: 38supporting
confidence: 52%
See 1 more Smart Citation
“…The chemical shift of L3 lines likely results from oxygen vacancies, which partially decrease the oxidation states of Fe cations from Fe 3+ to Fe 2+ . 44,45 By comparing the degree of chemical shift of L3 lines, it can be concluded that Fe2O3-S has the maximum amount of oxygen vacancies, followed by Fe2O3-C and Fe2O3-R, in accordance with the result of oxygen K-edge energy loss ( Figure 6A). 3.3.…”
Section: 38supporting
confidence: 52%
“…44 Figure 6A represents the EELS spectra of oxygen K-edge energy-loss near-edge fine structure (ELNES) for Fe2O3-S, Fe2O3-C, and Fe2O3-R. Four peaks, denoted as a, b, c, and d, can be found in all materials. 44 In general, a derives from the O 1s to 2p core level hybridized with the Fe 3d orbital, and b originates from the O 2p states hybridized with the transition 44,45 It is obvious that the intensities of a and b of Fe2O3-S are lower than those of Fe2O3-C and Fe2O3-R samples (Fe2O3-S < Fe2O3-C < Fe2O3-R). The intensity decreases of a and b are caused by the oxygen vacancies inside the prepared materials, resulting in diminish-ing hybridization of metal 3d and O 2p orbits.…”
Section: 38mentioning
confidence: 99%
“…In comparison, the specific activity of the Au/commercial iron oxide catalyst is lower at 1.46 mol CO ⋅g Au −1 ⋅h −1 . Furthermore, from Table , it can be observed that the Au/PB‐350 catalyst shows better catalytic performance than Au‐loaded commercial Fe 2 O 3 and some previously reported oxide‐supported Au catalysts ,,,…”
Section: Introductionmentioning
confidence: 74%
“…However, the CO conversion rate was dramatically reduced to around 30% when the GHSV was increased to 1 L min −1 , and it was further reduced to between 10 to 20% when the GHSV was further doubled to 2 L min −1 . The considerable decrease in CO conversion rates of these catalysts with increasing GHSV is caused by the reduced residence time of the reactants on the surface of these catalysts at higher GHSV ,. The specific catalytic activity of the Au‐loaded nanoporous iron oxide cubes was calculated and compared with those of previously reported catalysts as shown in Table .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation